Die österreichische Dezemberverfassung 1867: Konstitutionalismus – Grundrechte – Gerichtsbarkeit des öffentlichen Rechts - Olechowski, Thomas (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2019)
With the so-called Austro-Hungarian Comprimise of 1867, the Habsburg monarchy was profoundly transformed. In December 1867, a new constitution came into force in the non-Hungarian part of the monarchy, and this constitution lasted until the end of Austria-Hungary in 1918. It followed largely constitutional principles. The Reichsrat, however, was much more an assembly of estates than a modern constitutional parliament. A series of electoral reforms changed the character of this assembly. The fundamental rights and the public jurisdiction were regulated in an exemplary way The December Constitution also promised equality to all tribes before the law. This commandment was in practice but repeatedly disregarded.